Uso de escala de autoeficácia para análise da capacidade de puérperas para a amamentação - Machado, Maria Luiza Camuri (2017)
While aspects associated to benefits, duration and problems of breastfeeding are widespread in the scientific environment, issues related to selfefficacy in the breastfeeding process are still little addressed. Objective: To describe the self-efficacy for breastfeeding of postpartum women attended in a Health Insurance Plan. Material and Method: A descriptive, exploratory study with quantitative approach was developed with puerperal women who attended a course of birth preparation or were linked to a private health plan in the city of São José do Rio Preto , SP. Those with single, full-term newborns with good vitality at birth and hospital discharge were included. A socioeconomic questionnaire and breastfeeding selfefficacy scale (BSES-VB) were used for data collection. Results: A total of 98 postpartum women participated in the study. Of the participants, 32.7% were covered by health care plans, but did not participate in the course offered to pregnant women. Women who participated in the course of pregnant women had significantly higher selfefficacy in breastfeeding compared to those who did not participate. The level of selfefficacy was: 42.9% "high"; 27.5% "average" and 29.6% "low". The highest selfefficacy scores were observed among the exclusively breastfed women (69.4%). The technical domain had a higher score when compared to the intrapersonal domain score. Conclusion: The course offered to pregnant women proved to be relevant as a tool of great importance for the positivity of self-efficacy. These data have stood out the importance of the obstetrical nurses' performance in this setting, field of study, on the teaching / learning process on breastfeeding, a role that comprises multiple actions in the development of specific competences, reception, motivation and orientation, thus, improving the increase of compliance as well as the duration of breastfeeding . This research was performed in the field of a Nursing master degree program, Faculdade de Medicina de São José do Rio Preto (FAMERP). “Breastfeeding Self- Efficacy as assessed by the BSES: a literature review” and “Use of the Breastfeeding Self-Efficacy Scale (BSES) in the analysis of breastfeeding confidence” were both the papers produced on the theme.